Rancang Bangun Aplikasi Pencarian Pendonor Darah Berbasis Android - Robertus Sanjaya; Ester Lumba (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to create an Android application that can speed up delivery the information of donor search, by giving notifications to application users who have the same blood type as the patient. The development of this application uses development method Rational Unified Process (RUP), by implementing the Google API to set the location, and calculate the distance between the user and the donor's location. The Firebase Cloud Messaging service is also implemented for sending notifications when there is a new information of donor search, the notification can be received by users with the blood type that needed, either in an open or closed application. Besides being able to share information about donor needs, users can also inform the agenda of events such as blood donations, to other users in the application.